The Scientific Concept of Wetlands in the Creation of Delta del Paraná Ramsar Site, Argentina - Levrand, Norma-Elizabeth (2023)
In 2016, a portion of the Paraná Delta was registered under the terms of the Ramsar Convention on Wetlands of International Importance, Especially as Waterfowl Habitat (UNESCO 1971). Our purpose is to investigate the context of production and the meaning of the scientific concept of wetlands, essential to characterize and frame the site within said Convention. Using qualitative methodology, based on documentary analysis and semi-structured interviews with key actors (officials and experts), the epistemic development of the concept in the international sphere is described, as well as its admission and adaptation processes in the Argentine national sphere, and its connection to the designation of the Paraná Delta site. As a result, it is noted that in the scientific field, the notion of wetlands has stabilized. It was translated into a current definition in an international treaty and a definition agreed upon and adapted to the situation of wetlands in Argentina. The actions of the experts and the identification of the Paraná Delta as a wetland promoted the site's inscription on the list established by the Ramsar Convention.